Divine Science: Ar-Razy's Trailblazing Perspective on Al-Fatihah's Scientific Secrets - Mubarok, Fahmi Ulum Al; Azani, Mohammad Zakki; Salim, Hakimuddin; Abdulhakim, Luqman; Kurniawan, Beni (Syntax Literate, 2024)
This research aims to explore the contributions of Ar-Razi in integrating religious values with scientific findings, particularly in his interpretation of Surah Al-Fatihah. Through his scientific and critical exegesis method, Ar-Razi provides a fresh perspective on the relationship between religion and science, elucidating scientific discoveries encompassing the existence of a multi-dimensional universe, natural elements, and divine education in the creation of humans, plants, as well as the placement of planets and stars. The research results indicate that integrating religious values with scientific findings deepens the understanding of Quranic verses and provides solid arguments for the truth of the holy scripture. The significance of scientific discoveries in proving the truth of the Quran further strengthens the moral foundation of society, creating harmony between the material and spiritual dimensions. This research contributes insights into the relationship between religion and science, offering an ethical framework for scientific development. Additionally, it has the potential to inspire the development of scientific exegesis methods for understanding sacred texts, serving as a guide for future researchers in bridging the gap between religious values and scientific discoveries, fostering a holistic understanding of the world that combines material and spiritual dimensions.